2021
DOI: 10.1080/13510002.2021.1937456
|View full text |Cite
|
Sign up to set email alerts
|

Validation of magnetic resonance relaxometry R2 value and cyst fluid iron level for diagnosis of ovarian endometrioma

Abstract: Objectives: Magnetic resonance (MR) R2 relaxometry is a safe, noninvasive diagnostic modality for the evaluation of iron levels in the contents of ovarian cysts. The study aims to investigate the sensitivity and specificity of the two methods, R2 value and iron level, in diagnosing OMA patients in the validation set. Methods: A prospective cohort study was conducted from 2013 to 2019. We investigated how R2 value was affected by iron-related compounds, antioxidants and bioelements in the cysts. Results: The se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The accuracy of this categorization, however, remains to be verified, since the appearance may be a mere reflection of hormone responsiveness or aberrant angiogenesis of the lesions. Two studies investigating specific iron-sensitive MRI techniques as a diagnostic tool for endometriomas ( Takahashi et al, 1996 ; Imanaka et al , 2021b ) also confirmed higher iron levels in endometriomas via cyst fluid sampling.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…The accuracy of this categorization, however, remains to be verified, since the appearance may be a mere reflection of hormone responsiveness or aberrant angiogenesis of the lesions. Two studies investigating specific iron-sensitive MRI techniques as a diagnostic tool for endometriomas ( Takahashi et al, 1996 ; Imanaka et al , 2021b ) also confirmed higher iron levels in endometriomas via cyst fluid sampling.…”
Section: Resultsmentioning
confidence: 82%
“…The iron content of ovarian endometriomas is well studied, with 11 papers reporting on the iron concentrations in this tissue ( Takahashi et al , 1996 ; Iizuka et al , 1998 ; Yamaguchi et al , 2008 ; Singh et al , 2013 ; Sanchez et al , 2014 ; Benaglia et al , 2015 ; Guo et al , 2015 ; Yoshimoto et al , 2015 ; Nagayasu et al , 2020 ; Imanaka et al , 2021a , b ). The findings of Benaglia et al (2015) , Sanchez et al (2014) , Nagayasu et al (2020) , and Singh et al (2013) are summarized elsewhere in this review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation